Histoid hansen's with transepidermal elimination: Five cases - Supekar Bhagyashree Babanrao; Suyash Singh Tomar; Vaishali Hainath Wankhade; Lavanya Panindra; Rajesh P Singh; Dharitri Bhat (International Journal of Mycobacteriology, 2022)
Histoid leprosy is an expression of multibacillary leprosy with unique histopathology and characteristic bacterial morphology. It is characterized by the occurrence of asymptomatic firm, dome-shaped succulent papulonodules on apparently normal skin, or subcutaneous tissues. There are very few reports of the detection of Mycobacterium leprae in the epidermis in leprosy, which may have a possible role in transmission. We report five de novo cases of histoid leprosy with transepidermal elimination.